FROM STRATEGIC BUSINESS UNIT TO INTERFIRM SRATEGIC BUSINESS UNIT: A THEORETHICAL FRAMEWORK TO IBU PERFORMANCE AND PLACEMENT - Garbelli, Maria (European Scientific Journal, ESJ, 2014)
Global manufacturing businesses manage a flexible use of time and space, in order to take the most of different manufacturing locations: thus, companies are pressed to search for manufacturing solutions that can combine both manufacturing time and spatial requirements, in order to control and guard the most convenient global areas with own strategic manufacturing units. Businesses face competition also by associating with other businesses, creating a competitive network by stressing many and intense relationships: two or more companies achieve mutual advantage by giving up the absolute control they held over certain business processes, to exploit common benefits generated by their association. This realize a radical re-thinking of their whole organization: through a massive recourse to outsourcing strategies – with the aim to take the best from the market by developing complex mechanisms aimed to implementing the competitive relationships either ‘individually’ or in association with other businesses (suppliers, distributors, or even competitors) – internal skills undergo a progressive reduction until the ‘core business’ remains under strict control. The shared activities can be realized in interfirm business units, representing the smallest part of a cooperative network. In this paper we examine the fundamental international literature on alliances and network, finding a new perspective on interfirm business units placement and performance evaluation